The Development of Fall Prevention Model of The Elderly through Community Participation - Klinhom, Wichuda; Nimit-arnun, Nongpimol; Wattakiecharoen , Jeuajan; Thipkaew, Chonlathip (Journal of The Royal Thai Army Nurses, 2020)
This study aimed to develop participatory fall preventive model for community-dwelling elderly people in Ratchaburi province. The integration of community empowerment and health risk communication was applied as a study framework. The mixed-method design was applied by using among 150 participants of key persons during May-December 2019. The data were collected through quality approved instruments; including a set of open-ended questions, balancing screening test, environment risk assessment, and fall preventive behavior questionnaire. A paired t-test was used to examine the difference mean scores of quantitative data, while content analysis technique was used for qualitative data. The findings revealed that the effectiveness of collaborative fall preventive model. The key success factors were the significant communication channel through public forum and health volunteers, towards friendly climate and active working team. This model consisted of 1) situational analysis and vision 2) multi-factorial intervention campaign 3) process evaluation and monitoring and 4) Summarization. Moreover, after joining the intervention program, the samples’ fall preventive behavior improved, as did their physical balance significantly. Thus, the suggestion is to be reinforce the community continuingly for growing up their strength of those related to fall prevention strategies development.